Self‐perceived burden to others as a moral emotion in wishes to die. A conceptual analysis. (21st May 2019) - Rehmann‐Sutter, Christoph
Abstract: Patients at the end of their life who express a wish to die sometimes explain their wish as the desire not to be a burden to others. This feeling needs to be investigated as an emotion with an intrinsically dialogical structure. Using a phenomenological approach, two key meanings of the feeling of being a burden to others as a reason for a wish to die are identified. First, it is an existential suffering insofar as it contains the perception of a plight so desperate that it can only be relieved by the end of the patient's existence. Second, it is an empathic concern that implies caring about those who bear the burden of caring for the person at the end of their life. It is therefore a moral emotion, encompassing a series of difficulties, including the subjective perception of a stark imbalance between giving and taking, the adequacy of the representation of the caregiver burden in the patient's mind, and the danger of diminishing the worth of one's life out of shame or self‐denigration. R. D. Laing's terminology of crossed perspectives in interexperience is used to systematically distinguish the actual caregiver burden, the patient's view of the caregiver burden, the stress for the patient in feeling that s/he is a burden to the caregiver, and the caregiver's view of the patient's stress. The sense of being a burden implies the belief that the caregiver feels burdened, and the fear that this burden could become unbearable.